Characterizing patients hospitalized without an acute care indication: A retrospective cohort study. Issue 4 (9th February 2023) - Rosenthal, Molly A.; Ranji, Sumant R.; Kanzaria, Hemal K.; Ortiz, Gabriel M.; Chase, Jack; Chodos, Anna H.; Nguyen, Oanh K.; Rodriguez, Eric G.; Makam, Anil N.
Abstract: Background: Hospitalizations by patients who do not meet acute inpatient criteria are common and overburden healthcare systems. Studies have characterized these alternate levels of care (ALC) but have not delineated prolonged (pALC) versus short ALC (sALC) stays. Objective: To descriptively compare pALC and sALC hospitalizations—groups we hypothesize have unique needs. Designs, Settings, and Participants: A retrospective study of hospitalizations from March‐April 2018 at an academic safety‐net hospital. Main Outcome and Measures: Levels of care for pALC (>3 days) and sALC (1–3 days) were determined using InterQual©, an industry standard utilization review tool for determining the clinical appropriateness of hospitalization. We examined sociodemographic and clinical characteristics. Results: Of 2365 hospitalizations, 215 (9.1%) were pALC, 277 (11.7%) were sALC, and 1873 (79.2%) had no ALC days. There were 17, 683 hospital days included, and 28.3% ( n = 5006) were considered ALC. Compared to patients with sALC, those with pALC were older and more likely to be publicly insured, experience homelessness, and have substance use or psychiatric comorbidities. Patients with pALC were more likely to be admitted for care meeting inpatient criteria (89.3% vs. 66.8%, p < .001), had significantly more ALC days (median 8 vs. 1 day, p < .001), and were less likely to be discharged to the community ( p < .001). Conclusions: Patients with prolonged ALC stays were more likely to be admitted for acute care, had greater psychosocial complexity, significantly longer lengths of stay, and unique discharge needs. Given the complexity and needs for hospitalizations with pALC days, intensive interdisciplinary coordination and resource mobilization are necessary.